Genetic Rat Models of Parkinson's Disease. (5th April 2012) - Welchko, Ryan M.; Lévêque, Xavier T.; Dunbar, Gary L.
Abstract : Parkinson's disease (PD) is a neurodegenerative disease characterized by a specific loss of dopaminergic neurons. Although the vast majority of PD cases are idiopathic in nature, there is a subset that contains genetic links. Of the genes that have been linked to PD, α-synuclein and leucine-rich repeat kinase 2 have been used to develop transgenic rat models of the disease. In this paper we focused on the various transgenic rat models of PD in terms of their ability to mimic key symptoms of PD in a progressive manner. In general, we found that most of these models provided useful tools for the early stages of PD, but the development of new transgenic rats that present significant neuropathologic and motoric deficits in a progressive manner that more accurately mimics PD is needed.